Investigating EFL Teachers' Technology Adoption Level of ICT Integration by Using the Extended Technology Acceptance Model: A Study of MGMP Bahasa Inggris in Kutai Kartanegara - Annisa, Annisa; Suhatmady, Bibit; Rusmawaty, Desy (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Despite the widespread shift to digital learning during the pandemic, limited research has examined how contextual factors influence ICT adoption patterns among EFL teachers in developing regions. This study investigates Information and Communication Technology (ICT) adoption among 247 English as a Foreign Language (EFL) teachers in Kutai Kartanegara, Indonesia, using an extended Technology Acceptance Model (TAM) framework. The research addresses the critical gap in understanding technology integration patterns in post-pandemic Indonesian EFL education contexts.Using Structural Equation Modeling, the study examined core TAM constructs (perceived usefulness, perceived ease of use, attitude toward using, behavioral intention, and actual system use) alongside five extended constructs: digital self-efficacy, facilitating conditions, social influence, technology anxiety, and pandemic technology familiarity. Results revealed moderate-to-high ICT adoption levels, with video conferencing tools achieving the highest adoption rates, particularly Zoom, Google Meet, and WhatsApp for educational purposes. In contrast, AI-powered tools showed the lowest adoption rates, with limited integration in lesson planning activities. The extended TAM demonstrated superior explanatory power, accounting for 63% of variance compared to traditional models. All hypothesized relationships were supported, with perceived usefulness emerging as the strongest predictor of positive attitudes and digital self-efficacy significantly influencing perceived ease of use.Notable findings include persistent digital divides between beginner and advanced users, and the significant influence of pandemic technology familiarity on current adoption patterns, validating emergency remote teaching's lasting impact on educational practices. The study provides practical implications for differentiated professional development, infrastructure investment prioritizing reliable connectivity, and targeted interventions addressing confidence-building alongside technical training to enhance educational technology integration in developing regions